EP007/#994 Bay 1895344, a novel ATR inhibitor, demonstrates in vivo activity against ATRX altered uterine leiomyosarcoma. (4th December 2022) - Harold, Justin; Manavella, Diego; Bellone, Stefania; Siegel, Eric; Hartwich, Tobias; Zammataro, Luca; Mutlu, Levent; Altwerger, Gary; Menderes, Gulden; Ratner, Elena; Huang, Gloria; Clark, Mitchell; et al.
Abstract : Objectives: Uterine leiomyosarcoma (uLMS) is a rare, aggressive gynecologic malignancy. Up to 51% of uLMS harbor somatic mutations in ATRX, a tumor suppressor in the transcription regulation pathway, which increase sensitivity to ATR inhibitors. We sought to investigate the in vivo activity of a novel ATR inhibitor, BAY 1895344, against ATRX altered uLMS. Methods: ATRX altered PDX models LEY11 and LEY 16 were grafted into female CB-17/SCID mice and triaged to treatment with control or BAY1895344 (10 or 20 mg/kg daily). Treatments were given via oral gavage twice daily for three days weekly and tumor measurements and weights obtained twice weekly. ATR and DAXX expression were determined by Western blotting and RTPCR. Tumor volume differences were calculated with a two-way ANOVA, and p-value <0.05 was considered statistically significant. OS was compared via a Kaplan-Meier survival curve. Results: Tumor growth inhibition was significantly greater in the BAY1895344 groups in both LEY 11 (n=12) and LEY 16 (n=13) (p=0.0003 and p = 0.006, respectively). Median overall survival was significantly longer in both LEY 11 (12.5 vs. 42 days, p = 0.001) and LEY 16 (32 vs. 60 days, p < 0.001). There was no significant toxicity. ATRX was overexpressed in LEY 11 (Avg dCt 10.09 vs. 6.56) as well as DAXX (Avg dCt 8.97 vs. 6.46). Conclusions: BAY1895344 demonstrates promising in vivo activity against a PDX model of uLMS that harbors ATRX mutations, with no significant toxicity. Phase I trials of BAY1895344 are currently ongoing, and its clinical use in uLMS warrants further investigation.